2017
DOI: 10.3892/mmr.2017.7006
|View full text |Cite
|
Sign up to set email alerts
|

The atrophy of white and gray matter volume in patients with comitant strabismus: Evidence from a voxel-based morphometry study

Abstract: To compare the difference in white matter volume (WMV) and gray matter volume (GMV) between the comitant strabismus (CS) patients and health controls by voxel-based morphometry (VBM) and the relationship with behavioral performance. A total of 20 patients with comitant strabismus (10 males and 10 females), and 20 healthy subjects (10 males and 10 females) with matched age, sex status underwent magnetic resonance examination. The authors analyzed the original 3D T1 brain images using the VBM module. The comitan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 31 publications
2
42
0
Order By: Relevance
“… 39 , 40 Researches of strabismus subjects suggested that white matter volume was reduced in the right precuneus in the comitant strabismus patients. 41 Nevertheless, Yang et al found a significant increase of the bold signal in the bilateral precuneus in the patients with infantile esotropia, 42 and cortical activations in intermittent exotropia were found in right precuneus. 23 In the present study, we detected an increased ALFF in the right precuneus of SA group.…”
Section: Discussionmentioning
confidence: 96%
“… 39 , 40 Researches of strabismus subjects suggested that white matter volume was reduced in the right precuneus in the comitant strabismus patients. 41 Nevertheless, Yang et al found a significant increase of the bold signal in the bilateral precuneus in the patients with infantile esotropia, 42 and cortical activations in intermittent exotropia were found in right precuneus. 23 In the present study, we detected an increased ALFF in the right precuneus of SA group.…”
Section: Discussionmentioning
confidence: 96%
“…Voxel-based morphometry of magnetic resonance imaging (MRI) data involves the normalization of all image spaces into the same stereotactic space, and extraction of gray matter (GM), white matter (WM), and cerebrospinal fluid (CSF), smoothing, and, finally, statistical analysis to determine the differences between groups (Thomas & Bahaei, 2012). The voxel-based morphometry (VBM) technique has been used in ophthalmic diseases such as amblyopia, strabismus, glaucoma, and optic neuritis (Barnes et al, 2010;Huang et al, 2016;Li et al, 2012;Ouyang et al, 2017).…”
mentioning
confidence: 99%
“…Similarly, we assumed that the functional abnormalities in the POS might be connected with visuomotor abnormalities such as pointing errors in XT patients 34 . Besides functional alteration, recent microstructural studies have confirmed grey matter atrophy in the POS of patients with strabismus 35 …”
Section: Discussionmentioning
confidence: 91%